Novas tecnologias na educação: uma análise do Moodle do Nuteia - Cruz Junior, José Antonio Fonteles (2013)
With the expansion of the new technologies, routines and social spheres are affected. The society always develop technologies that served of tool for the realisation of tasks, of the more Simple to the most complex. All the technologies developed until then brought like consequence impacts in the walk of this society and with the new technologies It is not being different. However, the leverage and changes that these devices impose on the contemporary society possess singular characteristics and, besides that, His field of impact is gigantic owed his countless applicabilities in the social spheres. The aim of this work, in the first moment, is to understand this contemporary stage splitting of the theoretical analyses of Castells, Levy, Santaella, Read and Recuero. After understood this current society, split for the theoretical analysis of the impacts of these new technologies in the field of the education. For this, Moran and Machado will be the main theorists. At last, after visualising, of theoretical and practical form, through investigations of institutes and newspapers recognised, arrive to the big aim that is to analyse of practical form, but with knowledge theoretical, like the IESAM (instituito Of upper education of the Amazônia), through the Moodle, if use of a new technology for pedagogical ends and communicational for the upper education